BOTULISMO EM BOVINOS E OVINOS: EPIDEMIOLOGIA, CARACTERIZAÇÃO CLÍNICA, DIAGNÓSTICO LABORATORIAL, DIAGNÓSTICO DIFERENCIAL, ESTRATÉGIAS DE TRATAMENTO, CONTROLE E PREVENÇÃO - Juliana Paniago Lordello Neves (2021)
The use of feedlot system in beef cattle reduces animals’ slaughter age and improves productivity and meat quality. There are few studies regarding causes of mortality in cattle raised in this system in Brazil. Respiratory and digestive disorders are the main problems affecting these animals; neurological disorders are less common. Rabies has sporadic occurrence in feedlots and botulisms outbreaks have caused important losses. Chapter 1 – aims to describe epidemiology, clinical aspects, diagnostic procedure, and differentials diagnoses of experimental cases of botulism in sheep, and to evaluate prevention and treatment protocols. Two experimental trials were made to reproduce the disease in sheep, using a re-hydrated corn that was previously associated to an outbreak in cattle. In the first study, 18 animals were used, and it was not possible to reproduce the disease. In the second experiment, four sheep received, orally, saline solution with carcasses of cattle that had died from botulism. Two of the four sheep were previously vaccinated against the disease. The four sheep got sick and were treated with commercial antitoxin, but three of them died. Chapter 2 – aims to describe a botulism outbreak occurred in feedlot cattle, showing diagnosis and treatment barriers of the disease in this situation. A large outbreak of botulism took place in Midwestern Brazil in August 2017, with feedlot steers fed with corn silage, contaminated with Clostridium botulinum neurotoxic type C (BoNT/C). The onset of the outbreak occurred 15 days after 1,700 steers started to be fed with contaminated corn silage. A total of 1,100 steers were affected and 1,090 of them died within four days. Ten steers recovered after being treated with antitoxin. No gross or microscopic lesions were found in affected steers. The diagnosis was based on epidemiological data, characteristic clinical signs, and positive mouse bioassay results. Chapter 3 – aims to describe a rabies outbreak in feedlot cattle, reinforcing the importance of differential diagnosis and institution of preventive protocols. The outbreak occurred in Mato Grosso do Sul, Midwestern Brazil, and eight cattle died; four were necropsied on site, and four were sent to the Federal University of Mato Grosso do Sul. These animals were not vaccinated against rabies. Animals presented neurological disorders, and one also showed self-inflicted trauma. The necropsy findings were similar in all animals – enlarged urinary bladder and hyperemic leptomeninges. Microscopic findings were perivascular infiltrate of lymphocytes and plasm cells, mild gliosis, and intracytoplasmic inclusion bodies in neurons (Negri bodies). All eight were positive in direct immunofluorescence test.